Should the 'outs' join the European banking union? - Pia Hüttl; Dirk Schoenmaker (Bruegel, 2016)
[Highlights] For political reasons, European Union member states' opinions on joining banking union range from outright refusal to active consideration. The main stance is to wait and see how the banking union develops. The wait-and-see positions are often motivated by the consideration that joining banking union might imply joining the euro. However, in the long term, banking union's ultimate rationale is linked to cross-border banking in the single market, which goes beyond the single currency. This Policy Contribution documents the banking linkages between the nine `outs' and 19 `ins' of the banking union. We find that some of the major banks based in Sweden and Denmark have substantial banking claims across the Nordic and Baltic regions. We also find large banking claims from banks based in the banking union on central and eastern Europe. The United Kingdom has a special position, with London as both a global and European financial centre. We find that the out countries could profit from joining banking union, because it would provide a stable arrangement for managing financial stability. Banking union allows for an integrated approach towards supervision (avoiding ring fencing of activities and therefore a higher cost of funding) and resolution (avoiding coordination failure). On the other hand, countries can preserve sovereignty over their banking systems outside the banking union.
Keywords: 330